2015
DOI: 10.1111/vox.12317
|View full text |Cite
|
Sign up to set email alerts
|

Additive solutions differentially affect metabolic and functional parameters of platelet concentrates

Abstract: Resuspension of platelets in Intersol for 7 days results in increased platelet activation and platelet metabolism compared with SSP+® or Composol®. Further clinical studies are needed to evaluate whether the observed differences in PAS-PCs affect the recovery rate or the life span of transfused platelets.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
37
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(46 citation statements)
references
References 26 publications
7
37
2
Order By: Relevance
“…The concentration of sCD40L and sCD62P varied significantly over time in PCs; however, their increases were more substantial in PPCs than SDA‐PCs. Moreover, the level of sCD40L was greater in SDA‐PCs stored in PAS‐D than those in SDA‐PCs stored in PAS‐E, consistent with previous reports . Storage of platelets in PAS has a number of benefits, including a reduction of serious adverse reactions .…”
Section: Discussionsupporting
confidence: 90%
“…The concentration of sCD40L and sCD62P varied significantly over time in PCs; however, their increases were more substantial in PPCs than SDA‐PCs. Moreover, the level of sCD40L was greater in SDA‐PCs stored in PAS‐D than those in SDA‐PCs stored in PAS‐E, consistent with previous reports . Storage of platelets in PAS has a number of benefits, including a reduction of serious adverse reactions .…”
Section: Discussionsupporting
confidence: 90%
“…Disappearance of glucose in Amicus PCs suggests that the energy needs exceeded their capacity for oxidative metabolism . With the depletion of glucose on Day 7 on the Amicus platform, a decline in glycolysis may occur . Previous studies confirm the importance of glucose consumption and lactate production as they correlate to in vivo PLT survival and recovery .…”
Section: Discussionmentioning
confidence: 90%
“…An Amicus platform study showed the presence of glucose until the end of storage . Disappearance of glucose in Amicus PCs suggests that the energy needs exceeded their capacity for oxidative metabolism . With the depletion of glucose on Day 7 on the Amicus platform, a decline in glycolysis may occur .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various platelet additive solutions have been compared in several studies and found to have an effect on the product quality . Platelets stored in newer generation PASs have an improved quality compared to the ones stored in PAS B.…”
Section: Introductionmentioning
confidence: 99%